Ring-Fused meso-Tetraarylchlorins as Auspicious PDT Sensitizers: Synthesis, Structural Characterization, Photophysics, and Biological Evaluation - Laranjo, Mafalda; Pereira, Nelson A. M.; Oliveira, Andreia S. R.; Campos Aguiar, Márcia; Brites, Gonçalo; Nascimento, Bruno F. O.; Serambeque, Beatriz; Costa, Bruna D. P.; Pina, João; Seixas de Melo, J. Sérgio; Pineiro, Marta; Botelho, M. Filomena; et al. (Frontiers in Chemistry, 2022)
Novel 4,5,6,7-tetrahydropyrazolo[1,5-a]pyridine-fused meso-tetraarylchlorins, with different degrees of hydrophilicity (with methyl ester, hydroxymethyl, and carboxylic acid moieties), have been synthesized and their photophysical characterization as well as in vitro photocytotoxicity assessment against human melanoma and esophageal and bladder carcinomas was carried out. An integrated analysis of the photosensitizers’ performance, considering the singlet oxygen generation data, cell internalization, and intracellular localization, allowed to establish relevant structure-photoactivity relationships and the rationalization of the observed photocytotoxicity. In the diacid and monoalcohol series, chlorins derived from meso-tetraphenylporphyrin proved to be the most efficient photodynamic therapy agents, showing IC50 values of 68 and 344 nM against A375 cells, respectively. These compounds were less active against OE19 and HT1376 cells, the diacid chlorin with IC50 values still in the nano-molar range, whereas the monohydroxymethyl-chlorin showed significantly higher IC50 values. The lead di(hydroxymethyl)-substituted meso-tetraphenylchlorin confirmed its remarkable photoactivity with IC50 values below 75 nM against the studied cancer cell lines. Subcellular accumulation of this chlorin in the mitochondria, endoplasmic reticulum, and plasma membrane was demonstrated.